Evaluating the Effectiveness of Explainable Artificial Intelligence Approaches (Student Abstract) - Jung, Jinsun; Kim, Hyeoneui (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
Explainable Artificial Intelligence (XAI), a promising future technology in the field of healthcare, has attracted significant interest. Despite ongoing efforts in the development of XAI approaches, there has been inadequate evaluation of explanation effectiveness and no standardized framework for the evaluation has been established. This study aims to examine the relationship between subjective interpretability and perceived plausibility for various XAI explanations and to determine the factors affecting users' acceptance of the XAI explanation.